Unilateral retinitis pigmentosa: 30 years follow-up - Weller, Julia M.; Michelson, Georg; Jünemann, Anselm (BMJ Case Reports, 2014)
This case report depicts the clinical course of a female patient with unilateral retinitis pigmentosa (RP), who presented first in 1984 at the age of 43 years. At the beginning, there were cells in the vitreous leading to the diagnosis of uveitis with vasculitis. Within 30 years, the complete clinical manifestation of RP developed with bone spicule-shaped pigment deposits, pale optic disc, narrowed arterioles, cystoid macular oedema, posterior subcapsular cataract, concentric narrowing of the visual field and undetectable electroretinogram signal. At the age of 72 years, there are still no signs of retinal dystrophy in the other eye.
EVALuna2:21211